Acquisition of /s/ clusters in Croatian speaking children with phonological disorders - Mildner, Vesna (Array, 2010)
We studied the acquisition of nine #sC clusters in 30 Croatian-speaking phonologically disordered children, aged between 3 ; 8 and 7 ; 0 years, by analyzing their renditions of target words elicited in response to visual stimuli presented on a computer screen. Results did not support the idea that a greater jump in sonority from C1 to C2 would translate into a greater accuracy of productions. The percentage of correct realizations was high for ‘ /s/+nasal’ combinations (mean 85%), and for approximants /j/ and /v/ (mean 77%) and stops (mean 73%), with significantly lower scores for liquids /l/ and /r/ (mean 47%). The difference between SSP-violating and SSP-following targets was not significant, and neither was the homorganicity of the target. The most frequent errors were substitution of the first consonant (i.e. /s/) while keeping the second one. These children are significantly different from the typically developing group in two ways. First, retention of the first or the second consonant is not as frequent, and second, /l/ is almost as difficult as /r/, as opposed to the typically developing children who had no more difficulty with /l/ than with the other two approximants. Although cluster reduction is not the most common process in erroneous productions, the patterns emerged here generally agree with the findings from other languages